Calculating of stress intensity factors of soldered joints with multiple cracks - Al Emran Ismail; Saifulnizan Jamian; Kamarul Azhar Kamarudin; Mohd Khir Mohd Nor; Mohd Norihan Ibrahim; Ahmad Mubarak Tajul Arifin; Mohd Fahrul Hassan; Mohd Rasidi Ibrahim; Mohammad Zulafif Rahim (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This paper presents the solution of stress intensity factors of multiple cracks at the joint between two materials. Based on the literature survey, there are tremendous number of works found on the study of edge and central cracks. On the other hand, several papers on the multiple cracks can be also be found in open literature. However, the work on multiple cracks with different crack sizes are hard to find. Therefore, this paper focuses to study the crack interaction obtained from different crack sizes. ANSYS APDL is used to model and solve the problems considering the cracks embedded in the plain strain plate under tension stress. There are two important parameters are considered such crack sizes and mechanical mismatches between joint and based materials. Since the crack is symmetrical, only a quarter model is used and verified. Based on the numerical simulation, it is found that two factors are significantly affected the multiple cracks at the joints such as mechanical mismatches and relative crack sizes.